PENGARUH FEE AUDIT DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Ismail, mira; Arman, Andi; Mellisyah, Mellisyah; Muhaimin, Muhaimin; Muttiarni, Muttiarni; Salam, Salam (Media Mahardhika, 2024)
This quantitative research focuses on examining the impact of audit fees and firm size on tax avoidance. Secondary data, specifically financial reports published on www.idx.co.id, is utilized for this study. The population consists of mining companies, and purposive sampling is employed to select a sample of 138 companies. The analysis is conducted using the e-views software. The results indicate a positive and significant influence of audit fees on tax avoidance. A high audit fee does not imply a company's willingness to comply with tax regulations, but rather companies aim to minimize potential fiscal correction effects that may inflate profits. Proactive measures are taken to mitigate the impact, ensuring that the taxes paid are not excessively high. Additionally, firm size shows a positive and significant impact on tax avoidance